ANALISIS DESAIN SISTEM GRID PENTANAHAN PLTU BERAU KALIMANTAN TIMUR 2 X 7 MW - Syamsir Abduh; Mulia Sulistiani (Jetri : Jurnal Ilmiah Teknik Elektro, 2014)
To be able to secure and safety the equipment and the workers who work in the power plant area Berau 2 x 7 MW, of course, required the earthing system design quality, reliable and efficient whereby the grounding grid resistance, voltage step and touch voltage according to the calculations contained in IEEE Std 80 -2000. This research will discuss the evaluation of system design with respect to the value of earthing resistance grounding grid, mesh voltage and step voltage. Evaluation parameters - parameters according to calculations published in IEEE Std 80-2000. Results from this study is the need for improvements to the design value of the voltage step and touch voltage is actually one - each 219.03 V and 383.29 V, which is greater than the voltage step and touch voltages are allowed each - amounting to 164.86 V for weight 50 kg; 223.13 V for weights 70 kg and 128.21 V to weight 50 kg; 173.53 V to 70 kg weight. Keywords: grounding system, touch and step voltage, conductor areaSistem  pentanahan  yang  berkualitas,  handal  dan  efisien adalah merupakan  persyaratan utama dalam merancang suatu  sistem pentahanan untuk dapat mengamankan peralatan dan para pekerja di area pembangkit. Makalah ini bertujuan untuk menganalisis desain Grid Pentanahan  PLTU Berau 2x7 MW oleh Konsultan Perencana berdasarkan metode  IEEE Std 80-2000. Analisis dilakukan terhadap  beberapa  parameter  berupa  luas  penampang  konduktor,  nilai  tahanan  grid  pentanahan  tegangan sentuh dan tegangan langkah.  Hasil dari penelitian menunjukkan bahwa  perlu adanya perbaikan desain dengan nilai tegangan langkah dan tegangan sentuh sebenarnya masing – masing 219,03 V dan 383,29 V, yang lebih besar dari tegangan langkah dan tegangan sentuh yang diperbolehkan masing – masing sebesar 164,86 V untuk bobot 50 kg; 223,13 V untuk bobot 70 kg dan 128,21 V untuk bobot 50 Kg;173,53 V untuk bobot 70 Kg. Kata kunci: Grid  pentanahan,  Tegangan  langkah,  Tegangan   Sentuh, Luas   penampang konduktor